Hematological and serum biochemical indices of West African dwarf goats with foreign body rumen impaction (2012)
Hematological and biochemical parameters were determined in 82 West African Dwarf goats with foreign body rumen impaction (FBR) and 40 normal WAD goats without foreign body rumen impaction (WFBR) in order to evaluate their influence on the etio-pathogenesis of rumen impaction. The mean PCV (26.22%), RBC (9.03 X 106/µL), Hb (8.38g/dl) and MCHC (32.20g/dl) were significantly lower (P<0.05) in FBR than in WFBR. The values obtained for serum sodium, potassium, calcium and magnesium in FBR goats were not significantly different (P<0.05) from that of WFBR goats. Mean values of serum total protein (4.02gm/dl), phosphorus (3.38mg/dl), glucose (29.33gm/dl), zinc (0.72mmol/L) and copper (0.49mmol/L) in FBR goats were significantly lower than in WFBR goats. The results suggest that foreign body rumen impaction in WAD goats is influenced by some hematological (PCV, RBC, Hb, MCHC) and serum biochemical (total protein, phosphorus, glucose, zinc, copper) parameters and can be used as a basis for formulating preventive measures.